ENHANCING BPK RI'S AUDIT DESIGN FOR PEOPLE'S WELFARE: A PRACTICAL APPROACH - Suartama, I Kadek; Nurdin, Syamsul; Susilo, Fakhridho SBP (Badan Pemeriksa Keuangan Republik Indonesia, 2015)
The 2016-2020 Strategic Plan of BPK RI necessitates audits to be conducted to advance people's welfare to the greatest extent possible as a reflection of the growing maturity of BPK RI as an accountability organization. This would require BPK RI to be able to examine and evaluate whether the government's development programs under RPJMN have achieved the desired outcomes or impact of increasing people's welfare. This paper aimed to find a practical approach to enhance BPK RI's audit design in order to be able to contribute to the optimization of people's welfare as required under the new vision of Renstra 2016- 2020. The authors use their experience on the recent formulation of BPK RI's Audit Policy 2016- 2020 (Kebijakan Pemeriksaan 2016-2020), in which the authors are actively involved. The authors also use reviews of existing audit design and study on the relevant theoretical and academic literature that provide the overarching study framework. The study concluded that BPK audits should be designed toward national development programs in RPJMN 2015-2019 which correlate directly with or possessing great leverage in the achievement of welfare indicators. AbstrakRenstra BPK 2016-2020 mensyaratkan pemeriksaan-pemeriksaan BPK dilaksanakan sedemikian rupa sehingga dapat mendorong terwujudnya pembangunan untuk sebesar-besar kemakmuran rakyat sebagai refleksi dari peningkatan kematangan BPK. Pemeriksaan BPK diharapkan mampu menilai dan mengevaluasi apakah program-program pembangunan yang didesain atau ditetapkan dalam RPJMN telah mencapai outcome maupun dampak yang diinginkan yaitu meningkatkan kesejahteraan masyarakat. Studi ini bertujuan untuk mencari pendekatan praktis untuk memperkuat desain audit BPK agar dapat berperan untuk meningkatkan kesejahteraan rakyat seperti yang disyaratkan dalam Rentstra 2016-2020. Penulis menggunakan pengalaman profesional dalam membangun formula Kebijakan Pemeriksaan BPK 2016-2020, dimana penulis terlibat aktif dalam penyusunannya. Selain itu penulis juga menggunakan reviu atas desain audit yang ada saat ini serta studi literatur dalam sebagai bahan analisa studi. Hasil studi menyimpulkan bahwa pemeriksaan BPK seharusnya di desain untuk sesuai dengan RPJMN2015-2019 yang berhubungan langsung dengan indikator kesejahteraan.